2020
DOI: 10.1021/acsomega.0c03505
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of an Asymmetric Perylene Diimide in Terms of Hydrosolubility, G-Quadruplex Binding, Cellular Uptake, and Telomerase Inhibition in Prostate Cancer Cells

Abstract: Perylene diimide (PDI) derivatives have been studied as G-quadruplex ligands that suppress telomerase activity by facilitating G-quadruplex formation of telomeric DNA and the hTERT promoter. PIPER, the prototypical PDI, reduces telomerase activity in lung and prostate cancer cells, leading to telomere shortening and cellular senescence of these cells. However, PIPER suffers from poor hydrosolubility and the propensity to aggregate at neutral pH. In this report, we synthesized a new asymmetric PDI, aPDI-PHis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…As demonstrated in our previous publication, aPDI−PHis, an asymmetric perylene diimide derivative with a 2-aminoethylpiperidine side chain and a histidine side chain, is superior to its symmetric counterparts in terms of hydrosolubility, G4 binding, cellular uptake, and telomerase inhibition in prostate cancer cells. 28 Hydrosolubility of PMIs and PIPER. Perylene diimide derivatives (PDIs) with basic side chains often aggregate at neutral to basic pH.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As demonstrated in our previous publication, aPDI−PHis, an asymmetric perylene diimide derivative with a 2-aminoethylpiperidine side chain and a histidine side chain, is superior to its symmetric counterparts in terms of hydrosolubility, G4 binding, cellular uptake, and telomerase inhibition in prostate cancer cells. 28 Hydrosolubility of PMIs and PIPER. Perylene diimide derivatives (PDIs) with basic side chains often aggregate at neutral to basic pH.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We previously found that PM2 and aPDI−PHis suppressed telomerase activity and hTERT expression at lower concentrations than PIPER, despite the comparable cellular uptake. 23,28 Therefore, we opted to modify our perylene G4 DNA Binding Study by Spectrophotometry. Telomerase activity in cancer cells can be suppressed through G-quadruplex formations at the hTERT promoter and the 3′overhang of the telomere.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations